Model Pembelajaran CTL (Contextual Teaching And Learning) Pada Mata Pelajaran PAI dan Implementasinya di SMP Islam Asysyakirin Pinang Kota Tangerang - EE Junaedi Sastradiharja; Siskandar Siskandar; Irtifa’an Khoiri (PMPP Lembaga Penelitian dan Studi Kebijakan, 2020)
This research is a qualitative descriptive study, the subjects in this study are the principal of Asysyakirin Middle School, WAKA Curriculum, Homeroom 7.4 and Islamic Subjects. Data collection techniques used are: observation, and interviews. This research was conducted from August to October 2018. The results of this study showed that some Islamic Religious Education teachers in Asysyakirin Middle School had understood the meaning of the contextual learning model, the teacher just needed to deepen and gradually introduced the CTL (Contextual Teaching and Learning) learning model to student. The implementation of Islamic Religious Education learning more or less has reflected the application of the CTL (Contextual Teaching and Learning) learning model which includes 5 principles and 7 pillars of contextual learning, with the results of implementing the components of the CTL (Contextual Teaching and Learning) learning model as follows: interest (related), direct experience (esprecing), application (appliying), cooperation (cooperating), transfer of knowledge (transfering), constructivism (contruktivisem), finding (inquiry), asking (questioning), learning communities (learning comunity), modeling (modeling), reflection (reflection), true assessment (authentic assessment). It is expected that all teachers can use active learning, to develop the learning process one of them by using the CTL learning model, because the implementation of CTL can activate students in the learning process and increase student motivation. Because there are still inhibiting factors in the implementation of CTL, it is expected to frequently attend seminars and workshops and frequently read books related to CTL learning to better master and deepen how the application of CTL is good and right. So that it can improve the quality of education on an ongoing basis and establish better interactions to be able to achieve the expected learning goals